AB1467-HPR Measurement of cervical proprioception in patients with axial spondyloarthritis. (12th June 2018) - Ozen, T; Tonga, E.; Polat, M.G.; Akar, S.
Abstract : Background: Axial spinal inflammation and spinal posture disorders in axial spondyloarthritis (axSpA) may deteriorate proprioception which may be caused by pathologic involvement of spinal entheses containing proprioceptive afferents. 1 Cervical spine is one of the main inflammation area in axSpA. 2 Impaired cervical proprioception has negative effects on postural control system. 3 The cervicocephalic relocation mesure by laser pointer is found a reliable method to measure cervical sensory function in healty participants in a recent study. 4 And there is limited data that regarding cervical proprioception in axSpA. Objectives: To examine the differences in cervical joint proprioception between patiens with axSpA and healthy subjects. Methods: The cervical joint position errors (JPE) were measured to evaluate proprioceptive function accuracy in patients with 29 axSpA and 21 healthy subjects by laser pointer with cervical application. Neutral head position method was used to evaluate proprioception in flexion, extension, rotation and lateral flexion in right and left movement directions at sitting position (figure 1). 5 Three measures were performed, and the average of the three trials was used for analysis. The distance between zero spot and joint position which patient had been reconstructed was measured by centimetre. Spinal mobility evaluated by BASMI, function evaluated by BASFI and HAQ-S; disease activity defined by BASDAI, pain and fatigue were evaluated by VAS. Results: There were 29 patients (21 men, mean (±SD) age; 41.4±10.9 years) and 21 healthy subjects (15 men, mean age 41.1±11.3 years). BASMI, HAQ-S and fatigue score were significantly higher in patients (BASMI values were 3.9±2.3 vs 1.3±0.7, p<0.001; HAQ-S values were 2.1±0.8 vs 0.8±0.2, p<0.001; fatigue values were 37.2±23.3 vs 16.2±14.9, p=0.001). The comparison of cervical JPE showed significantly larger errors (p<0.05) in patients with axSpa, except right rotation (p=0.166) (table 1). Conclusions: Cervical joint position sense is impaired in subjects with axSpa. Proprioceptive training may help to boost the effectiveness of rehabilitation. References: [1] Pompeu JE, Romano RS, Pompeu SM, Lima SM. Revista brasileira de reumatologia. 2012;52(3):409–16. [2] Madsen OR. Rheumatol Int. 2018. doi: 10.1007/s00296–017–3920–1. [3] Malmström EM, Fransson PA, Jaxmar Bruinen T, Facic S, Tjernström F. Exp Brain Res. 2017;235(9):2755–2766. [4] Hatamvand S, Ghiasi F, Asgari Ashtiani A.R, Akbari A, Hossienifar M. International Journal of Medical Research & Health Sciences, 2016, 5, 7S:598–603. [5] Alahmari K, Reddy RS, Silvian P, Ahmad I, Nagaraj V, Mahtab M. Braz J Phys Ther. 2017;21(4):259–267. Disclosure of Interest: None declared